Socioeconomic and epidemiological milieu of maternal death due to eclampsia in West Bengal, India: A mixed methods study - Md Illias Kanchan Sk (Wiley, 2023)
Abstract Background West Bengal is experiencing an unanticipated risk of eclampsia among pregnant women and it persists as the leading cause of maternal mortality. This study aimed to investigate the predictors for maternal deaths due to eclampsia in West Bengal. Methods The study adopted retrospective mixed methods covering facility and community‐based maternal death review approaches. Facility‐based data were used for 317 deceased cases wherein the community‐based review approach was used in 40 cases. An in‐depth interview was also performed among 12 caregivers. Results One‐third of maternal deaths occurred due to eclampsia, and this accounted for the leading cause of maternal deaths in West Bengal. A younger age, a primigravida or nulliparous status, absence of antenatal care (ANC), and residence in rural areas appeared to have the highest risk of developing eclampsia. The majority of pregnant women had an irregular antenatal check‐up history, particularly during the second trimester of pregnancy. The rate of eclampsia‐related maternal death was higher in women residing more than 49 km from the studied hospitals. Most of the deceased women were referred to three or more hospitals before their death. Gravidity, the number of ANC visits, the mode of delivery, and delays at different levels were significant confounders of death due to eclampsia. The risk of death due to eclampsia was two times higher among women without ANC and those who had a cesarean section than that in their counterparts. Conclusions Women in West Bengal have a high risk of preeclampsia and eclampsia resulting in maternal mortality and morbidity. Gravidity, the number of ANC visits, the mode of delivery, and delays in recognition of eclampsia contribute to the risk of maternal deaths. The establishment of separate eclampsia units, enhanced screening, and preventive and treatment procedures may optimize managing eclampsia.